Procedure of Gender Change - Krzyżewski, Łukasz (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Lately in Poland the topic of transgender is rising to the higher ranks then before. These paper presents legal aspect of sex change in Poland which is one of a few countries that does not address that issue in the statutory form but has only resolved it by jurisprudence. Author presents current procedure of changing gender in Poland and history of its evolution over the years. Procedure of sex change has been fully developed by jurisprudence based on art. 189 of the Civil Procedure Code which made numerous problems arise. All of them require addressing and will be covered in this article. Paper also shows most important judicature of The European Court of Human Rights and international law regarding transsexualism and legal aspects of it. Author concludes the paper by pointing necessary steps that Polish legislator should take in discussed matter.